2021
DOI: 10.1002/mnfr.202000745
|View full text |Cite
|
Sign up to set email alerts
|

Lycium ruthenicum Anthocyanins Attenuate High‐Fat Diet‐Induced Colonic Barrier Dysfunction and Inflammation in Mice by Modulating the Gut Microbiota

Abstract: Scope: Gut barrier dysfunction and inflammation originating from a dysbiotic gut microbiota (GM) are strongly associated with a high-fat diet (HFD). Anthocyanins from Lycium ruthenicum (ACs) show antiobesity effects through modulating the GM. However, the mechanism linking the antiobesity effects of ACs and GM modulation remains obscure. Methods and results: To investigate the ameliorative effects of ACs on colonic barrier dysfunction and inflammation, mice are fed an HFD with or without ACs at doses of 50, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 72 publications
12
93
1
Order By: Relevance
“…Serum LPS content can reflect the change of intestinal permeability, and then reflect the level of gut microbiota disorders [ 53 ]. HFD feeding can promote the proliferation of endotoxin-producing bacteria [ 54 ]. Meanwhile, HFDs can increase the permeability of the intestinal mucosal barrier, causing more LPS to enter the circulatory system and promoting systemic inflammation and obesity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum LPS content can reflect the change of intestinal permeability, and then reflect the level of gut microbiota disorders [ 53 ]. HFD feeding can promote the proliferation of endotoxin-producing bacteria [ 54 ]. Meanwhile, HFDs can increase the permeability of the intestinal mucosal barrier, causing more LPS to enter the circulatory system and promoting systemic inflammation and obesity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several species in the family Lactobacillaceae were linked to body weight reduction in HFD-induced obese mice [ 63 ], and intervention with polyphenols significantly increased the abundance of Lactobacillaceae [ 64 , 65 ]. However, the relative abundance of Lactobacillaceae was elevated in mice fed a HFD, while the amount of this family of bacteria was lowered in the mice treated with anthocyanins (anthocyanins from the fruits of L. ruthenicum ) in a recent study [ 66 ]. Our findings also revealed that P3G treatment reduced the relative abundance of Lactobacillaceae, even though there was no significant difference between the NC and HFD groups ( Figure 4 E).…”
Section: Discussionmentioning
confidence: 99%
“…HFD can induce an increase in intestinal permeability in mice or rats with decreased mRNA or protein expression of TJ including claudins-1, claudins-2, claudins-3, and ZO-1 [ 114 , 115 , 116 , 117 ]. More specifically, in IL-10 knockout mice with IBD, IBD-like colitis is spontaneously triggered with an increase in intestinal permeability [ 118 ].…”
Section: Hfd and Bile Acidsmentioning
confidence: 99%